Caribbean New Orleans : empire, race, and the making of a slave society - Vidal, Cécile (North Carolina scholarship online., 2020)
Combining Atlantic and imperial perspectives, Caribbean New Orleans offers a portrait of the city and an investigation of the French colonists who established racial slavery there, and the African slaves who were forced to toil for them. Casting early New Orleans as a Caribbean outpost of the French Empire rather than as a North American frontier town, Cecile Vidal reveals the persistent influence of the Antilles which shaped the city's development through the 18th century. She urges us to rethink our usual divisions of racial systems into mainland and Caribbean categories. Drawing on New Orleans's rich court records as a way to capture the words and actions of its inhabitants, Vidalexplores the challenges that slow economic development, Native American proximity, imperial rivalry, and the urban environment posed to a social order that was predicated on slave labor and racial hierarchy.